2020
DOI: 10.1080/13562517.2020.1742681
|View full text |Cite
|
Sign up to set email alerts
|

Short-term, short-changed? A temporal perspective on the implications of academic casualisation for teaching in higher education

Abstract: The increasing casualisation of academic labour over recent years has been noted across the global north. In the UK, this takes a number of forms, including fixed term, hourly paid and zero hours contracts. What tends to characterise them all, however, is a focus on the shortterm. In this paper, we draw on a qualitative study with 20 UK-based academics on casualised contracts to consider the implications of the short-term nature of such employment for teaching and pedagogy. We come to this with a temporal pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…In line with the literature on uncertainties (Leathwood -Read 2020, Ivancheva 2019, Bernardi et al, 2008, Blossfeld et al 2005) and the phenomenon of the neoliberal universities (Rosa 2021), labour market and workplace uncertainties crucially affected the WLB of female PhD students in this research. Women experienced the global phenomenon of precarity that has reached the highly prestigious institutions of research and development in Hungary as well.…”
Section: Rq1: Constraining and Facilitating Factorssupporting
confidence: 60%
See 1 more Smart Citation
“…In line with the literature on uncertainties (Leathwood -Read 2020, Ivancheva 2019, Bernardi et al, 2008, Blossfeld et al 2005) and the phenomenon of the neoliberal universities (Rosa 2021), labour market and workplace uncertainties crucially affected the WLB of female PhD students in this research. Women experienced the global phenomenon of precarity that has reached the highly prestigious institutions of research and development in Hungary as well.…”
Section: Rq1: Constraining and Facilitating Factorssupporting
confidence: 60%
“…Youths and women are particularly exposed to it due to their unstable socio-economic status, including precarious employment: short fixed-term work contracts and low incomes even in prestigious jobs (Leathwood -Read 2020, Ivancheva et al 2019, European Commission 2012, Bernardi et al 2008. Childbearing decisions under such circumstances are complex, and women, as an adaptive strategy, often delay the milestones of their family formation.…”
Section: Gendered Life Coursesmentioning
confidence: 99%
“…However, Maryam also explores how those in junior or insecure positions are less likely to push pedagogic boundaries. This is supported by Leathwood and Read (2020) who researched the pedagogic decision-making of academics on casualised contracts and found that this produced short-term temporal logics that had negative impacts on inculcating critical pedagogies as opposed to more instrumental, outputdriven teaching. While Prevent may present itself as a neutral technology to understand and challenge radicalisation, as an entangled apparatus, it materialises itself in bodies differently and is shaped by who feels 'at home' (Ahmed, 2012) in higher education institutions, disciplines and classrooms.…”
Section: Tanisha Southern Citymentioning
confidence: 92%
“…My position as a feminist scholar committed to social justice in the current climate creates additional layers of uncertainty and concerns about backlash (Ringrose 2018). Challenging working conditions and fear of job loss constrains what is possible in terms of innovation, critique and boundary pushing (Leathwood and Read 2020;Morris et al forthcoming). Nevertheless, I concur with Burke and Carolissen (2018), that educators hold responsibilities to identify pedagogical strategies which enable moments of resistance in this context.…”
Section: Methodsmentioning
confidence: 99%